Recent Trends in Nanocarrier-Based Targeted Chemotherapy: Selective Delivery of Anticancer Drugs for Effective Lung, Colon, Cervical, and Breast Cancer Treatment. (2nd July 2020) - Jin, Ke-Tao; Lu, Ze-Bei; Chen, Jin-Yang; Liu, Yu-Yao; Lan, Huan-Rong; Dong, Hai-Ying; Yang, Fan; Zhao, Yuan-Yuan; Chen, Xiao-Yi
Abstract : Chemotherapy drugs are cytotoxic to tumor cells, but their lack of specificity leads to a range of side effects. The off-target effects of such drugs can be improved through the use of nanoparticles (NPs). Administered NPs show enhanced accumulation in tumor tissue near the blood vessels, enhancing both anticancer drug permeability and tumor retention. Several nanocarriers are now approved for clinical use in a range of cancer therapies, and many novel formulations are in the later stages of clinical trials. Here, we describe the advances in this area through the review of novel NP drug formulations developed over the last year. We focus specifically on lung, colon, cervical, and breast cancers and discuss the future of NPs as potential treatment options in these areas.